Acute exacerbation of ocular graft-versus-host disease and anterior uveitis after COVID-19 vaccination - Lin, Chen-Yu; Chien, Hung-Jen (BMC ophthalmology, 2023)
Background To report a case of simultaneous occurrence of acute exacerbation of ocular graft-versus-host disease (GVHD) and anterior uveitis following coronavirus disease 2019 (COVID-19) vaccination. Case presentation A 60-year-old man with primary myelofibrosis and GVHD after receiving allogeneic hematopoietic stem cell transplantation (HSCT), developed acute exacerbation of ocular GVHD and anterior uveitis after receiving first dose of COVID-19 vaccine. The patient developed erythema of the eyelids, conjunctival hyperemia, superficial punctate keratopathy, and prominent anterior chamber inflammation in both eyes. The ocular GVHD and anterior uveitis were managed with mainly topical corticosteroids, antibiotics, lubricants, and systemic corticosteroids, but were difficult to control. Intravitreal injection of dexamethasone was administered, and the inflammation gradually subsided 6 months after the onset of initial symptoms. Conclusions Clinicians should be aware of rare refractory anterior uveitis and acute exacerbation of ocular GVHD after COVID-19 vaccination in patients undergoing HSCT. Early diagnosis and aggressive treatment should be considered to reduce the likelihood of severe complications. Keywords: Hematopoietic stem cell transplantation, Graft-versus-host disease (GVHD), Anterior uveitis, Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), Coronavirus disease 2019 (COVID-19) vaccination